2010
DOI: 10.1002/smll.200901364
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Efficiency of Nanostructured Graphene‐Based Photovoltaics

Abstract: Graphene-based organic photovoltaics (OPVs) have the potential for single-cell efficiencies exceeding 12% (and 24% in a stacked structure). A generalized equivalent circuit for OPVs is proposed and the validation of the proposed models is verified by simulation. The simulated short-circuit photocurrent density (computed using the simulated incident photon flux density and quantum yield), simulated current-voltage curve, and simulated 3D surface and 2D contour plots of solar-power-conversion efficiency versus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 51 publications
(63 reference statements)
1
64
0
3
Order By: Relevance
“…This is mainly because CNTs have poor solubility in organic polymer matrices and wide distributions in lengths and diameters. [171][172][173][174][175] Graphene has the advantage of higher electron mobility than that of C 60 derivatives as well as energy levels easily tunable by adjusting the material's size and functionality. Furthermore, graphene's large specific surface area and 2D structure favor the formation of a bicontinuous interpenetrating network of donor and acceptor at nanometer scale with maximum interfacial area.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
“…This is mainly because CNTs have poor solubility in organic polymer matrices and wide distributions in lengths and diameters. [171][172][173][174][175] Graphene has the advantage of higher electron mobility than that of C 60 derivatives as well as energy levels easily tunable by adjusting the material's size and functionality. Furthermore, graphene's large specific surface area and 2D structure favor the formation of a bicontinuous interpenetrating network of donor and acceptor at nanometer scale with maximum interfacial area.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
“…The unique sp 2 hybrid carbon nanostructure of GNs opens up new applications in nanoelectronics [3], biosensors [4,5], supercapacitors [6], and transistors [7]. Owing to their remarkable high electron mobility (15,000 cm 2 /V·s) [8], extremely large surface area (~2600 m 2 /g) [9], and low fabrication cost, GNs are considered as an ideal support for developing next-generation photovoltaic devices [10]. Li et al reported that on forming layered GNs-CdS quantum dots (QDs), the electrode exhibited a significant improvement in photo-response compared with that of single-walled carbon nanotube-CdS QD nanocomposites [11].…”
Section: Introductionmentioning
confidence: 99%
“…444 Thus far, graphene has not acted as a primary light absorber in OPVs or DSSCs even though such cells have been hypothesized to have PCE values of 12% in a single cell geometry and 24% in a tandem geometry. 445 However, graphene quantum dots (GQDs) have been employed as light absorbers inTiO 2 -based DSSCs as seen in Fig. 12g.…”
mentioning
confidence: 99%